“STAY THE HELL OUT OF IT”: GENERAL ARANA OSORIO, KISSINGER AND A FORGOTTEN CENTRAL AMERICAN CRISIS (1966-1974) (Tzintzun, Revista de Estudios Históricos, 2022)
This article examines the emergence and consolidation at the national andregional levels of Guatemalan general Carlos Arana Osorio. The article focuseson four elements: its political emergence, its contribution in building allianceswith other Central American presidents, its support to them in times of crisisunder the silent eye of the Nixon/Kissinger duo, and its role in confrontingdifferent domestic institutional areas to achieve the continuity of his politicalproject. It seeks to bring to light elements and temporalities usually overlookedin Central American historiography. Specifically, it seeks to discuss the politicalviolence in Guatemala and the Central American nuances within the LatinAmerican Cold War. This in order to nuance the classical canon that emphasizesviolence and US interventionism as axis of politics in the country.
Keywords: Cold War; Nixon Doctrine; Kissinger; authoritarianism